Toponymic elements in the Turkistan-Turkmen Sahra Manuscript of "The Book of Dede Korkut" - Ekici, M. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
Among the most distinctive works of the Turkish epic tradition are the manuscripts containing the sayings, poetic passages, and epic narratives attributed to Dede Korkut. Four manuscripts of these works are known today. Rich in language, literature, history, and folklore, they form an essential part of Turkic cultural heritage. The third manuscript, known as the Turkistan Türkmen Sahra Manuscript of Dede Korkut, holds particular significance due to its abundance of toponymical (place name) elements. The manuscript studies the place names found in this manuscript. First, the place names appearing in the twenty-three poetic passages are presented, followed by those occurring in the epic narrative titled “Salur Kazan’s Slaying of the Seven-Headed Dragon.” These are organized and categorized in tables. At the end of the study, the cultural significance of the identified place names within the context of Turkish culture is discussed, without delving into etymological analysis. The researcher categorizes place names under three main headings: natural features (land, water, mountains, passes), cities, and countries or regions. These toponyms encompass a wide geography from China to Europe and from Siberia to India, reflecting the lands, capitals, and cultural environments historically inhabited by Turkic peoples.